2021
DOI: 10.1108/hff-01-2021-0036
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of external explosion characteristics induced by indoor natural gas vented explosion

Abstract: Purpose The purpose of this paper is to ascertain the harm to personnel and equipment caused by an external explosion during natural gas explosion venting. The external explosion characteristics induced by the indoor natural gas explosion are the focal points of the investigation. Design/methodology/approach Computational fluid dynamics technology was used to investigate the large-scale explosion venting process of natural gas in a 6 × 3 × 2.5 m room, and the characteristics of external explosion under diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 34 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…The gas explosion accident in coal mines has a serious harm, so scholars around the world have carried out a more comprehensive study on gas explosion. Pang et al 11 studied the explosion suppression technology of CH 4 /air by detonating different concentrations of CH 4 /air with an electric spark inducer. It was found that the methyl-rich nutrient inorganic salt spray can inhibit the explosion of CH 4 /air.…”
Section: Introductionmentioning
confidence: 99%
“…The gas explosion accident in coal mines has a serious harm, so scholars around the world have carried out a more comprehensive study on gas explosion. Pang et al 11 studied the explosion suppression technology of CH 4 /air by detonating different concentrations of CH 4 /air with an electric spark inducer. It was found that the methyl-rich nutrient inorganic salt spray can inhibit the explosion of CH 4 /air.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of chemical industry parks (chemical clusters), the tank area, as an important area for the storage and transportation of chemical raw materials, intermediates and finished products, has shown a trend in recent years of having large-scale tanks and diversified storage types [ 1 ]. As the process pipelines in the tank area are various and complex, and most of the storage media are hazardous chemicals with flammable and explosive characteristics, once leakage occurs, fire and explosion accidents are likely to occur [ 2 , 3 , 4 ]. The thermal radiation [ 5 , 6 ], explosion overpressure [ 7 , 8 ] and explosion debris [ 9 ] generated by these initial events, as well as the interaction between them, often lead to cascading domino accidents, causing serious casualties and property losses [ 10 ].…”
Section: Introductionmentioning
confidence: 99%